Development Of Bumdes Business Through Mosque Economic Business - Andi Rijal Kadir; A. Hadijah Sulfiyani A (ASHA Publishing, 2026)
Essentially, a Village-Owned Enterprise (BUMDesa) operates as a social enterprise, a business entity that actively seeks solutions to address social problems in the community. In this regard, social enterprises need to be distinguished from other socially oriented organizations and initiatives that benefit the community but are not businesses and rely more on aid. In the context of a BUMDesa, as a socially oriented institution, it is intended as part of the village government's primary duty to provide solutions to social problems within the community. However, when the Village Government is able to resolve these social problems through activities that generate added value in terms of profit, this becomes a distinct advantage for the Village Government. In the next concept, the presence of BUMDesa as an economic or profit-oriented institution generates Village Original Income (PADes). This situation should motivate the village government and all related parties to work together to formulate a strategy for establishing Village-Owned Enterprises as economic institutions in the village capable of realizing the true function of BUMDes, including job creation and absorption of the village's workforce. This can be realized when Bumdesa managers are given full authority through the Village Deliberation to optimize all potential, assets, community institutions, and resources within the village to transform them into business opportunities that can become profit-oriented business units for the advancement and sustainability of the Bumdesa. Based on the aforementioned background, using a strengths (discovery) approach to these potentials, the topic of discussion in this paper can be formulated: